Compromiso Laboral y su Efecto en el Desempeño del Personal en la Empresa Multimotos S.A - Palma Ronquillo, Livingstón Javier (2017)
he present investigation contains the analysis of the work carried out by the commercial company "Multimotos SA" in the city of Babahoyo, with the purpose of detecting the difficulties presented and possessed in human talent, preventing an optimal performance in their jobs, which is detrimental to the activity of the company. The purpose of this research arises from the lack generated by the lack of commitment and the effect it produces in an entire company, which seeks to explain the depth and seriousness with this particular problem that for many goes unnoticed